SIMULATION MODEL FOR RATIONAL UNIFIED PROCESS (RUP) SOFTWARE DEVELOPMENT LIFE CYCLE - Tuti Karen Tia (Sistemasi: Jurnal Sistem Informasi, 2019)
In software development there are several types of methodologies that can be used, one of which is Rational Unified Process (RUP). RUP is of software development process used in various software companies. There are various types of projects in RUP software development, small scale project, large-scale projects and re-engineering projects. Each type of project has different needs, especially in the use of each role. In RUP there are several important roles that cannot be done by an individual because they have to work at the same time. Basically the purpose of the RUP is to be able to produce high quality software. This cannot be achieved if the inappropriate role is used. This study proposes the number of roles needed for software development using RUP by creating simulation models. The purpose of simulation model is to determine the appropriate role based on each type of project. The results of the simulation model are in the form of a percentage of each role needed, the project manager has the largest percentage compared to other roles, which is 70% in small-scale projects and 65% in large-scale projects.